Future pathways to mainstreaming community energy. (December 2019) - Roby, Helen; Dibb, Sally
Abstract: The UK energy sector has been one of large-scale centralised energy production by big companies, with households seen as passive consumers of energy at the end of wires. The development of renewable energy technologies, such as solar photovoltaics (PV), signals greater potential for small-scale energy production. Such change provides the opportunity for households and communities to become active consumers and producers of energy, as well as for energy service providers to support integration of renewable technologies. Drawing on data from a community energy study, the paper shows how community energy projects can be test beds for developing new business models, leading to empowerment and democratisation as important stepping stones to mainstream community energy. The paper adds to existing knowledge about these challenges by developing possible future pathways to mainstream community energy: top-down; bottom-up; and hybrid. These pathways' potential contribution to decarbonising the energy sector is considered, with implications for policy, regulation and new business models. Highlights: New business models for community energy resulting from cuts in Feed-in-Tariffs. Hybrid pathways with local authorities and intermediaries to mainstream community energy. New roles for aggregators as intermediaries in community energy. Shift in concept of community energy to energy in the community.